Toxin Ct1a, from venom of Centruroides tecomanus, modifies the spontaneous firing frequency of neurons in the suprachiasmatic nucleus. (15th July 2021) - Alamilla, Javier; Jiménez-Vargas, Juana María; Galván-Hernández, Alan R.; Reyes-Méndez, Miriam E.; Bermúdez-Gúzman, Manuel J.; Restano-Cassulini, Rita; Olamendi-Portugal, Timoteo; Zamudio, Fernando Z.; Possani, Lourival D.; Valdez-Velázquez, Laura L.
Abstract: The peptide, denominated Ct1a, is a β-toxin of 66 amino acids, isolated from venom of the scorpion, Ce ntruroides tecomanus, collected in Colima, Mexico. This toxin was purified using size exclusion, cationic exchange, and reverse phase chromatography. It is the most abundant toxin, representing 1.7% of the soluble venom. Its molecular mass of 7588.9 Da was determined by mass spectrometry. The amino acid sequence was determined by Edman degradation and confirmed by transcriptomic analysis. Since neurons of the suprachiasmatic nucleus (SCN) maintain a spontaneous firing rate (SFR), we evaluated the physiological effects of toxin Ct1a on these neurons. The SFR exhibited a bimodal concentration-dependent response: 100 nM of Ct1a increased the SFR by 223%, whereas 500 nM and 1000 nM reduced it to 42% and 7%, respectively. Control experiments, consisting of recordings of the SFR during a time similar to that used in Ct1a testing, showed stability throughout the trials. Experiments carried out with denatured Ct1a toxin (500 nM) caused no variation in SFR recordings. Action potentials of SCN neurons, before and after Ct1a (100 nM) showed changes in the time constants of depolarization and repolarization phases, amplitude, and half-time. Finally, recordings of hNav1.6 sodium currents indicated that Ct1a shifts the channel activation to a more negative potential and reduces the amplitude of the peak current. These results all demonstrate that toxin Ct1a affects the SFR of SCN neurons by acting upon sodium channels of sub-type 1.6, implicating them in regulation of the SFR of SCN neurons. Graphical abstract: Image 1 Highlights: Ct1a is a β-toxin isolated from Centruroides tecomanus scorpion. Ct1a have an experimental molecular mass of 7588.9 Da and the full sequence are 66 amino acid residues length. The effect on the spontaneous firing rate by Ct1a, in the suprachiasmatic nucleus, is dependent on the concentration. Ct1a toxin changed the form of action potential of suprachiasmatic nucleus neurons. Ct1a toxin modifies the currents in hNav1.6. to more negative potentials and reduces the total amplitude.